Pendampingan Pembuatan Laporan Keuangan Berbasis Excel di Bunda Tarie Catering - Humaira, Balqis Al; Sari, Putri Netasya; Rahmadi, Zara Tania; Widjanarko , Widjanarko; Nurdiana, Diah; Yulianto, Kampono Imam; Utomo, Kabul Wahyu (PUAN INDONESIA, 2024)
This research aims to analyze the socialization process and practice of making Excel-based financial reports for micro, small and medium enterprises (MSMEs) in Cempaka Putih, Central Jakarta. The method used is a case study with a qualitative approach. Data was collected through in-depth interviews with MSME owners and financial managers as well as direct observation of the practices carried out in preparing financial reports. The research results show that intensive socialization and the practice of making Excel-based financial reports provide significant benefits for MSMEs in developing their financial understanding and skills.